2008
DOI: 10.13052/remn.17.597-611
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and control in precision mechanics

Abstract: This paper briefly describes three projects developed at the Active Structures Laboratory of ULB, in connection with precision mechanics. The first one considers the integration of piezoelectric fibers in composite structures for space applications; the second consists of an active piezoelectric bimorph mirror for adaptive optics, and the third considers the vibration isolation of sensitive payloads in spacecraft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…and then the displacement ductility ratio of abutments can be calculated based on the plastic hinge theory. According to the above specification content, while referring to the literature [25][26][27], the ratio µ2 of the allowable relative displacement of each limit state support to the relative displacement at shear strain y = 100% is used to determine its corresponding 4 damage states, i.e. : According to the definition of the bearing damage state obtained support at −40 • C when the damage index; through the support in the hightemperature displacement response calculation found that the support in 40 • C displacement value compared to room temperature increased by 19.4%, so according to the definition of the bearing damage state, the support in 40 • C when the damage index.…”
Section: Effect Of Temperature Forces On Bridge Susceptibilitymentioning
confidence: 99%
“…and then the displacement ductility ratio of abutments can be calculated based on the plastic hinge theory. According to the above specification content, while referring to the literature [25][26][27], the ratio µ2 of the allowable relative displacement of each limit state support to the relative displacement at shear strain y = 100% is used to determine its corresponding 4 damage states, i.e. : According to the definition of the bearing damage state obtained support at −40 • C when the damage index; through the support in the hightemperature displacement response calculation found that the support in 40 • C displacement value compared to room temperature increased by 19.4%, so according to the definition of the bearing damage state, the support in 40 • C when the damage index.…”
Section: Effect Of Temperature Forces On Bridge Susceptibilitymentioning
confidence: 99%